Law-braking and violence in the destinies of the "wish of ha ving a child" nowadays - Garcia, Edna Linhares (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
The following research suggests a reflection, from the psychoanalytic clinic and in a theoretical view by Piera Aulagnier, about the destiny of the wish of having a child nowadays, pointing to a law-braking and violence that repeatedly present themselves and form the contemporary sickness related to this wish.